How to Calculate Paired Sample t-Test using SPSS Software: From Step-by-Step Processing for Users to the Practical Examples in the Analysis of the Effect of Application Anti-Fire Bamboo Teaching Materials on Student Learning Outcomes - Afifah, Sakhiyyah; Mudzakir, Ahmad; Nandiyanto, Asep Bayu Dani (Indonesian Journal of Teaching in Science, 2022)
This study aims to demonstrate how to do paired sample t-test using SPSS software to analyze the effect of the application of anti-fire bamboo teaching materials on student learning outcomes. SPSS software is a very common statistical software in educational research that can be used to analyze the differences of a variable after being given treatment. One of the variables that can be analyzed is the difference in student learning outcomes. Teaching materials used in learning can cause differences in student learning outcomes. This research uses fire-resistant bamboo as multimedia-based teaching material to study the properties of the material and its changes. The results of the analysis using SPSS software showed that there are significant differences in student learning outcomes after using fire-resistant bamboo as multimedia-based teaching material. Student learning outcomes become improved and these teaching materials make it easier for students to understand the concepts being taught.